2005
DOI: 10.1039/b414181d
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption sites and rotational tunneling of methyl groups in cubic I methyl fluoride water clathrate

Abstract: Neutron spectroscopy in the meV and meV regime and quasielastic scattering is applied to characterize the dynamics of methyl groups of methyl fluoride guest molecules in cubic I CH 3 F-water clathrate. Only above T B 60 K quasielastic spectra are unaffected by quantum effects. They are well described by two Lorentzians representing the CH 3 F species in the small and large cages of the structure. The intensities show that both cages are completely filled. The linear broadenings with temperature follow the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
3
12
0
1
Order By: Relevance
“…Neutron diffraction analysis revealed that the CH 3 F hydrate formed SI. 18 Then, we considered that the CH 3 F molecules were enclathrated in both the 5 12 and 5 12 6 2 cages. The I L /I S values for the 2860 and 2960 cm -1 peaks were I L /I S ∼ 3.5 ((0.2) and 3.1 ((0.6) for, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Neutron diffraction analysis revealed that the CH 3 F hydrate formed SI. 18 Then, we considered that the CH 3 F molecules were enclathrated in both the 5 12 and 5 12 6 2 cages. The I L /I S values for the 2860 and 2960 cm -1 peaks were I L /I S ∼ 3.5 ((0.2) and 3.1 ((0.6) for, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Although the hydrogen atomso ft hese guestsa re not visible in these structures by means of PXRD,t he analytical resultsf or the rigid-body constraints suggestt hat the hydrogen atom of CH 3 F, CH 2 F 2 , and CHF 3 molecules point to the directions facing the hexagonal planes. Quantum rotational dynamics of methyl groups in CH 3 Fh ydratew ereo bserved by using neutrons pectroscopy under lower temperature conditions, below about 50 K. [32] The non-isotropic distribution of CH 3 Fw ithin the 5 12 …”
Section: Disorder Of Guest Moleculesmentioning
confidence: 99%
“…De plus, ces molécules invitées possèdent un axe de symétrie C 3 (la liaison C-X), leur conférant un caractère rotationnel 1-D et rendant la description mathématique (voir section précédente) beaucoup plus simple que celle du méthane (3-D). L'étude de la dynamique rotationnelle par effet tunnel est disponible dans la littérature pour des structures de type I formées avec les molécules de bromo-méthane [49], de fluoro-méthane [50] et de chloro-méthane [51]. Comme dans le cas du méthane, l'analyse des spectres est rendue complexe par le fait que les deux types de cages de la structure de type I sont remplies.…”
Section: Exemple De L'hydrate De Iodo-méthaneunclassified